The Effect of Motivation and Working Conditions on Employee Performance - Nurul Oktaviani Putri; Dudung Juhana (Journal of Economics, Management, and Entrepreneurship, 2023)
This study aims to investigate the impact of motivation and working environment on the performance of employees. The research methodology utilized in this study is a verificatory technique employing a survey methodology. The primary data utilized in this study consisted of questionnaires administered to employees of a fashion firm located in Bandung. The study consisted of a total of 35 participants. Through the utilization of path analysis and coefficient of determination analysis, the comprehensive data analysis demonstrated that motivation, working conditions, and employee performance were classified as somewhat satisfactory. The Rsquared value suggested a variance of 75.5%. Hence, it may be posited that employees' performance is impacted by motivation and the work environment, accounting for 75.5% of the variance, leaving the remaining 24.5% to be ascribed to undisclosed variables that have not been scrutinized. In addition, it is noteworthy that motivation exhibited a comparatively lesser impact, accounting for a total effect of 42.3%, in contrast to the working conditions, which yielded a total effect of 50.6%. Therefore, the organization must provide utmost importance to the work environment while simultaneously striving to enhance employee motivation. In summary, this research offers valuable perspectives on the correlation between motivation, working circumstances, and employee performance. The findings suggest that both elements substantially affect employee performance, with the work environment exhibiting a slightly more significant influence. Hence, organizations must prioritize the establishment of a supportive work environment alongside the cultivation and augmentation of employee motivation in order to attain maximum productivity.